Good Corporate Governance as a Variable Moderating the Effect of Information Asymmetry on Profit Management (An Empirical Study on Go Public Transportation and Logistic Companies in ISE during 2016-2019) - Atma Yuliana, Dias Candrika (Universitas Negeri Semarang, 2022)
This research aims to find out the effect of Information Asymmetry on profit management with GCG as moderating variable in transportation and logistic enlisted in ISE in 2016-2019. This research used multiple-linear regression analysis and MRA using Eviews 12 aid. The result of research can be summarized as follows: 1) Information asymmetry affects profit management significantly, and 2) Information asymmetry does not affect profit management with GCG being moderating variable. In this case, a moderating predictor type of moderation regression analysis model occurs, meaning that moderating variable serves merely as predictor in the relation established.